2002
DOI: 10.1097/00005373-200206000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Body Cooling by Cold Fluid Infusion Prolongs Survival Time during Uncontrolled Hemorrhagic Shock in Pigs

Abstract: In lightly anesthetized pigs during uncontrolled hemorrhagic shock, infusion with 4 degrees C lactated Ringer's solution (which seems to be feasible in the clinical setting) decreases the core temperature rapidly and prolongs survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
4
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 20 publications
0
27
4
1
Order By: Relevance
“…They thought this was a result of therapeutic hypothermia, which decreased HR and stroke volume index, and thus reduced oxygen demand of the heart. [2] In contrast, we found that cold fluid infusion decreased survival time. Cold fluid infusion may have increased volume and rate of hemorrhage, hypothermia, and acidosis, which might be related to poor tissue perfusion by causing vasoconstriction.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…They thought this was a result of therapeutic hypothermia, which decreased HR and stroke volume index, and thus reduced oxygen demand of the heart. [2] In contrast, we found that cold fluid infusion decreased survival time. Cold fluid infusion may have increased volume and rate of hemorrhage, hypothermia, and acidosis, which might be related to poor tissue perfusion by causing vasoconstriction.…”
Section: Discussioncontrasting
confidence: 57%
“…In the literature, there are only 2 studies that compare fluid resuscitation at different temperatures in HS model, and both of these were pig models. [2,10] Our study is the first to be conducted using rats. Norio et al [2] reported that cold fluid infusion increased survival time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations